Penerapan Pasal 3 Kode Etik Jurnalistik dalam Berita CNNIndonesia.com: (Studi Kasus Penembakan Wartawan Pada Perang Rusia-Ukraina) - Sahputra, Dedi; khairullah; Surbakti, Pernanda Marko; Ginting, Eka Sovyani br; Simanjuntak, Sindy Yohana; Marito, Sintia Hot (Jurnal Pekommas, 2023)
The war between Russia and Ukraine has received attention from the world's media, including in Indonesia. The purpose of this study was to find out the application of article 3 of the Journalistic Code of Ethics (KEJ) in reporting on the shooting of US journalists in the Russia and Ukraine war. This qualitative research uses a content analysis approach, namely research that has the nature of an in-depth discussion of the contents of written or printed information in the mass media, in this case, two CNNIndonesia.com news. The results of this study show that CNNIndonesia.com has tested the information they receive in the news by confirming it from several different sources. In terms of balance, the news is presented unequally. The news presented does not provide space or time for reporting proportionally to the Russian side. One of the two news headlines analyzed contains elements of judgmental opinion which are the journalist's personal opinion by making assumptions without news sources on these allegations. In terms of the principle of presumption of innocence, CNNIndonesia.com used the word ‘allegedly’ in the first news story about the perpetrators of the shooting of journalists in the Russia-Ukraine war. The use of these words prevents the news from being judged by the media (trial by the press)